PENGARUH PERGANTIAN AUDITOR, UKURAN PERUSAHAAN, LABA RUGI DAN SOLVABILITAS TERHADAP AUDIT REPORT LAG (SEKTOR INDUSTRI DASAR KIMIA, BARANG KONSUMSI DAN ANEKA INDUSTRI) - Junri Eliangsor Situmeang Junri; Wilisra Wilfrida Marbun; Risa Yunisa (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
The Basic Industry and Chemicals, Consumer Goods, and Various Industries sectors are companies that are developing very rapidly and well. Audit report lag is the time span for completing an annual financial statement audit, measured by the number of days required to obtain an independent auditor's report on the audit. the company's annual financial statements. The method used in this research is a quantitative approach, the type of this research is descriptive research and the nature of this research is cause and effect research. The data collection method used is to use documentation techniques. The data analysis method used is logistic regression. The population is all companies listed on the Indonesia Stock Exchange in the Basic and Chemical Industry Sector, Consumer Products and Various Industries. Determination of the sample in this study by looking at whether companies in the population report financial statements that have been audited on time or not. The results on the hypothesis show that auditor turnover, firm size, profit and loss and solvency simultaneously have no effect on audit report lag. The conclusion of this study is that simultaneously and partially auditor turnover, firm size, profit and loss and solvency have no significant effect on audit report lag.